Aplikasi Pgrouting Untuk Penentuan Jalur Optimum Pada Pembuatan Rute Pemadam Kebakaran (Studi Kasus : Kota Semarang) - Nasytha Nur Farah; Andri Suprayogi; Moehammad Awaluddin (Jurnal Geodesi UNDIP, 2014)
The technological developments of Geographic Information Systems (GIS) in integrating database processing operation has been very rapid. One of them is the use of SQL syntax which serves as a routing contained in PostgreSQL database. In pgRouting one of algorithm which is implemented is Dijkstra's algorithm. PgRouting is used to find out the optimum route from the starting point to the destination point which has been determined. In this study, pgRouting was applied to the Fire Company which requires timeliness in covering work areas in Semarang in case of fire.In order to use pgRouting, first install PostgreSQL, set up the data with a good quality control to be built in PostGIS and then add pgRouting extension itself. Furthermore, enable the required fields in the routing operations such as source, the target, length, topology, and index. After those required fields successfully activated, insert the SQL query in the SQL editor to implement the function of the shortest path by taking notice into the node source and the node target to be excecuted later on.The operation results are the shortest route layer along the attribute tables. And they are displayed on the Quantum GIS Wroclaw version by making the connection first. The results of dijkstra algorithm implementation are segments with weight/minimum cost from the starting node and aiming to the destination node. In the attributes which have been generated are also being taken notice the travel time problem. And it was analyzed to obtain the estimated time 1 that is 10 minutes and the estimated time 2 that is 15 minutes for the Firemen working. As the conclusion, that the Fire Company Central Office which is located in Jl.Madukoro has a strategic position to cover the area in Semarang City with the help of 2 Fire Company Sub Office which is located in Jl.Majapahit and Jl.Ngesrep Timur. But three districts namely Ngaliyan, Mijen, and Gunungpati are districts that is located beyond the reach of the office based on the analysis.Keywords: PostgreSQL, pgRouting, shortest path, Fire Route.